2018
DOI: 10.3390/min8100433
|View full text |Cite
|
Sign up to set email alerts
|

An Alternative Scenario on the Origin of Ultra-High Pressure (UHP) and Super-Reduced (SuR) Minerals in Ophiolitic Chromitites: A Case Study from the Mercedita Deposit (Eastern Cuba)

Abstract: The origin of the assemblage of ultra-high pressure (UHP), super-reduced (SuR) and several crustally derived phases in ophiolitic chromitites is still hotly debated. In this paper, we report, for the first time, this assemblage of phases in ophiolitic chromitites of the Caribbean. We studied the Mercedita chromitite deposit in the eastern Cuban ophiolitic complexes. The mineral phases were characterized using microRaman spectroscopy, energy-dispersive spectroscopy with a scanning electron microscope (SEM-EDS),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 82 publications
3
23
0
1
Order By: Relevance
“…Geochemical compositions and mineral chemistry characteristics of peridotites and chromitites from Greece have shown that the partial melting degree of primitive mantle and the hydrous nature of parent magma are major factors that control the compositional variations in them [10,18,19,42,45,56,57]. In addition, the known widespread geochemical heterogeneities in the bulk-rock compositions of chromitites from the Balkan Peninsula (Table 1) would be inconsistent with their evolution through simple partial melting processes, and suggest that their original geochemical compositions may have been modified by subsequent, post-magmatic processes taking place at shallow mantle depths [8,[66][67][68][69].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Geochemical compositions and mineral chemistry characteristics of peridotites and chromitites from Greece have shown that the partial melting degree of primitive mantle and the hydrous nature of parent magma are major factors that control the compositional variations in them [10,18,19,42,45,56,57]. In addition, the known widespread geochemical heterogeneities in the bulk-rock compositions of chromitites from the Balkan Peninsula (Table 1) would be inconsistent with their evolution through simple partial melting processes, and suggest that their original geochemical compositions may have been modified by subsequent, post-magmatic processes taking place at shallow mantle depths [8,[66][67][68][69].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the investigation of microdiamonds and graphite in chromite from ophiolite-type chromitites hosted in the Tehuitzingo serpentinite (southern Mexico), have been attributed a secondary origin and process related to the retrograde evolution of the respective chromitite. These processes apparently took place at relatively low temperatures (520-670 • C), at low pressures and in shallow depths [69]. The presence of minerals indicative of super-reducing phases, such as graphite-like, Fe-Ni-Cr alloys, awaruite (Ni 3 Fe), and heazlewoodite (Ni 3 S 2 ) [44,45,82,83], in the chromitite ores from the islands of Othrys and Skyros may be suggestive of the introduction of continental crust derived, reduced C-O-H fluids, during post-magmatic alteration processes.…”
Section: The Potential Role Of Abiotic Methane (Ch 4 )mentioning
confidence: 99%
See 2 more Smart Citations
“…In our view, the finding of diamonds is not stand-alone evidence for UHP unless additional UHP minerals are found. We would like to raise a warning flag to readers that many other minerals or features that are commonly used as indicators of UHP in ophiolitic chromitites (e.g., oriented lamellae of pyroxene in chromite) and associated super-reduced conditions in the deep mantle (e.g., moissanite, native elements, and alloys) did not necessarily form at these conditions (e.g., Pujol-Solà et al, 2018). Pujol-Solà et al reported these textures and minerals in chromitite bodies hosting (assimilating) unmetamorphosed gabbro sills in Cuban ophiolites, and concluded that these minerals did not form in the deep mantle, but as the result of cooling and serpentinization processes.…”
mentioning
confidence: 99%